Guidance to Support the Implementation of Specialized Adolescent and Young Adult Cancer Care: A Qualitative Analysis of Cancer Programs. Issue 9 (24th September 2022) - Haines, Emily; Asad, Sarah; Lux, Lauren; Gan, Hilary; Noskoff, Kara; Kumar, Bindu; Roggenkamp, Betty; Salsman, John M.; Birken, Sarah
Abstract : PURPOSE: The nearly 90, 000 adolescents and young adults (AYAs) diagnosed with cancer in the United States yearly have tended to occupy a no-man's land between medical and pediatric oncology, often reporting that existing models of care are misaligned with their needs and preferences. Although guidelines for optimal AYA cancer care are increasingly available, the implementation of such standards has been varied. This may be in part due to a lack of guidance for implementing specialized AYA care. In this study, we leveraged an implementation science framework to identify barriers and generate practical guidance to inform the implementation of specialized AYA cancer care. METHODS: We conducted semistructured qualitative interviews, guided by the Consolidated Framework for Implementation Research, with AYA care stakeholders (N = 32 from 14 cancer programs). Our multidisciplinary research team analyzed interview transcriptions using a template analysis approach and gleaned from interviews practical guidance for implementing specialized AYA care. RESULTS: Participants reported barriers to implementing specialized AYA care across all five Consolidated Framework for Implementation Research domains: (1) intervention characteristics (eg, costs), (2) inner setting (eg, difficulties in collaborating between pediatric and medical oncology), (3) outer setting (eg, patient-level barriers to participating in AYA services), (4) individual characteristics (eg, attitudes about AYA oncology), and (5) process (eg, lack of metrics for program evaluation). They also shared practical guidance for addressing these barriers. CONCLUSION: Emerging guidance on the core elements of AYA cancer care must be matched with guidance to support the implementation of specialized AYA care. This study contributes to the body of evidence available to inform future implementation efforts.